BUILDING RESILIENT AND INCLUSIVE MSMES: SYNERGIZING GOVERNMENT SUPPORT AND DIGITAL FINANCE ADOPTION - Erlinda Sholihah; Aftuqa Sholikatur Rohmania; Risma Nurhapsari; Ahmad Zaenuri (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2025)
This paper focuses on understanding the role of government support and digital financial adoption mediated by financial inclusion affecting the financial performance of Central Java’s MSMEs. This paper’s quantitative explanatory approach design is based on the Resource-Based Theory (RBT). Data were collected from 220 MSME actors through a simple random sampling method and analyzed using SEM-PLS by SmartPLS. The results indicate that government support, digital financial adoption, and financial inclusion significantly affect financial performance directly and indirectly. Theoretically, this study contributes to developing the RBT theory and practically becomes a reference for stakeholders in formulating strategies to improve the financial performance of MSMEs based on digital technology.